2019
DOI: 10.3390/app9214713
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Hardwood and Sugarcane Bagasse Biochar as Potting Mix Components for Container Tomato and Basil Seedling Production

Abstract: To investigate the potential of biochar as a propagation mix component, three experiments were conducted. A phytotoxicity test was conducted with water extract of sugarcane bagasse biochar (SBB), SBB mixes (10%, 30%, 50%, and 70% SBB with 30% perlite (P) and the rest being peat moss (PM); by vol.), mixed hardwood biochar (HB) mixes (10%, 30%, 50%, 70% and 100% HB with PM; by vol.), PM, P, 70%PM:30%P, and a commercial propagation mix (exp. 1). None of the mixes caused phytotoxicity. The same biochar mixes (exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Guo et al [62] found that the air space increased as the pine wood BC rate increased. Yu et al [63] indicated that the air space increased with the increasing mixed hardwood BC incorporation rate from 10% to 100% (by volume), but the trend was totally opposite for sugarcane bagasse BC. Another research showed that the substitution of peat with 10% (by volume) sewage sludge BC caused no difference on the air space in comparison with the 100% peat substrate control [64].…”
Section: Physical Properties Of the Container Substratesmentioning
confidence: 99%
“…Guo et al [62] found that the air space increased as the pine wood BC rate increased. Yu et al [63] indicated that the air space increased with the increasing mixed hardwood BC incorporation rate from 10% to 100% (by volume), but the trend was totally opposite for sugarcane bagasse BC. Another research showed that the substitution of peat with 10% (by volume) sewage sludge BC caused no difference on the air space in comparison with the 100% peat substrate control [64].…”
Section: Physical Properties Of the Container Substratesmentioning
confidence: 99%
“…Thus, even with the same feedstock, the properties such as surface area and pore volume will vary with temperature [35]. In addition, the application of biochar and the effects of the production of greenhouse seedlings or subsequent growth of seedlings have been less reported [34,36]. In the recent years, the field of seedling and potting horticultural plants has been significantly increased [37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…mixed hardwood BC with two composts resulted in similar or better basil and tomato plant growth compared to a peat moss-based commercial substrate. Similarly, Yu et al [26] showed that up to 70% (vol.) of mixed hardwood BC or sugarcane bagasse BC blended with peat moss can be used to grow container tomato and basil seedlings.…”
Section: Introductionmentioning
confidence: 82%